A Frail Liberty : Probationary Citizens in the French and Haitian Revolutions - Liu, Tessie P., 1955- (Book collections on Project MUSE., 2022)
"A Frail Liberty traces the paradoxical actions of the first French abolitionist society, the Societe des Amis des Noirs (Society of the Friends of Blacks), at the juncture of two unprecedented achievements of the revolutionary era: the extension of full rights of citizenship to qualifying free men of color in 1792 and the emancipation decree of 1794 that simultaneously declared the formerly enslaved to be citizens of France. This society helped form the revolution's notion of color-blind equality yet did not protest the pro-slavery attack on the new citizens of France. Tessie P. Liu prioritizes the understanding of the elite insiders' vision of equality as crucial to understanding this dualism. By documenting the link between outright exclusion and political inclusion and emphasizing that a nation's perceived qualifications for citizenship formulate a particular conception of racial equality, Liu argues that the treatment and status distinctions between free people of color and the formerly enslaved parallel the infamous divide between "active" and "passive" citizens. These two populations of colonial citizens with African ancestry then must be considered part of the normative operations of French citizenship at the time. Uniquely locating racial differentiation in the French and Haitian revolutions within the logic and structures of political representation, Liu deepens the conversation regarding race as a civic identity within democratic societies. "--